Influence of Angiotensin-Converting-Enzyme Gene Polymorphism on Echocardiographic Data of Patients with Ischemic Heart Failure - Duque,Gustavo Salgado (2016)
Abstract Background: Association between angiotensin-converting-enzyme (ACE) gene polymorphisms and different clinical and echocardiographic outcomes has been described in patients with heart failure (HF) and coronary artery disease. Studying the genetic profile of the local population with both diseases is necessary to assess the occurrence of that association. Objectives: To assess the frequency of ACE gene polymorphisms in patients with ischemic HF in a Rio de Janeiro population, as well as its association with echocardiographic findings. Methods: Genetic assessment of I/D ACE polymorphism in association with clinical, laboratory and echocardiographic analysis of 99 patients. Results: The allele frequency was: 53 I alleles, and 145 D alleles. Genotype frequencies were: 49.5% DD; 47.48% DI; 3.02% II. Drug treatment was optimized: 98% on beta-blockers, and 84.8% on ACE inhibitors or angiotensin-receptor blocker. Echocardiographic findings: difference between left ventricular diastolic diameters (ΔLVDD) during follow-up: 2.98±8.94 (DD) vs. 0.68±8.12 (DI) vs. -11.0±7.00 (II), p=0.018; worsening during follow-up of the LV systolic diameter (LVSD): 65.3% DD vs. 19.0% DI vs. 0.0% II, p=0.01; of the LV diastolic diameter (LVDD): 65.3% DD vs. 46.8% DI vs. 0.0% II, p=0.03; and of the LV ejection fraction (LVEF): 67.3% DD vs. 40.4% DI vs. 33.3% II, p=0.024. Correlated with D allele: ΔLVEF, ΔLVSD, ΔLVDD. Conclusions: More DD genotype patients had worsening of the LVEF, LVSD and LVDD, followed by DI genotype patients, while II genotype patients had the best outcome. The same pattern was observed for ΔLVDD.